Taxonomic and phylogenetic contributions to Fuscoporia (Hymenochaetales, Basidiomycota): two new species from Hawaii with a key to North American species - Chen, Qian; Liu, Lu; Si, Jing; Vlasák, Josef (Frontiers in Cellular and Infection Microbiology, 2023)
Fuscoporia is a cosmopolitan, poroid, wood-decaying genus, belonging to the Hymenochaetales. During a study of wood-inhabiting fungi in the USA, four unknown specimens were collected from Hawaii. Both morphological criteria and molecular genetic analyses based on the ITS+nLSU+EF1-α datasets and the nLSU dataset confirmed that these four specimens represent two new species of Fuscoporia, and they are described as F. hawaiiana and F. minutissima. Fuscoporia hawaiiana is characterized by pileate basidiocarps, the absence of cystidioles, hooked hymenial setae, broadly ellipsoid to subglobose basidiospores measuring 4−6 × 3.5−4.5 μm. Fuscoporia minutissima is distinguished by small pores (10−13 per mm) and basidiospores (3.4−4 × 2.4−3 μm). The taxonomic status of the two new species is briefly discussed. A key to the North American species of Fuscoporia is provided.